(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2012)
n its 23 years of existence, the Court has changed, society has changed, the judges have changed, but the ideal of striving for excellence in the provision of justice is still alive and kicking. There was a time when the Journal only contained case law, which today can be consulted on computers with just a click of the President’s mouse. For this reason, the Journal will have a different format and content, with preference given to doctrinal articles and commented case law. I encourage Substitute Federal Judges, Federal Judges and Federal Judges to write and submit their articles for publication in future editions of the Journal, as knowledge must be shared. I also invite all legal scholars who wish to collaborate. Current topics will be debated by jurists and scholars. Federal judges and legal experts will address various aspects of the same topic, encouraging debate, the analysis of divergent points of view, reflective capacity and the understanding and interpretation of reality in its entirety. Translated with DeepL.com (free version)